The description of two new species Helicometra pisodonophi sp. n. and Opecoelus haduyngoi sp. n. (Trematoda: Opecoelidae) from marine fishes in Ha Long bay, Vietnam - Ha, Nguyen Van (Academia Journal of Biology, 2012)
In the present paper, two new species of the family Opecoelidae Ozaki, 1925 from marine fishes collected in Ha Long bay, Vietnam, namely Helicometra pisodonophi sp. n. from Pisodonophis cancrivorus and Opecoelus haduyngoi sp. n. are described and illustrated. Description: Helicometra pisodonophi sp. n.: Body elongate-oval, 2,650 × 700 mm; oral sucker 270 × 300 mm; ventral sucker 450 × 430 mm; pharynx 105 × 115 mm; testes 2, lobed, contiguous, in posterior half of body, anterior 185 × 540, posterior 205 × 405 mm; cirrus-sac well developed, extends from just posterior to posterior margin of pharynx to middle region of ventral sucker; a irregular ovary, antero-sinistral to anterior testis, 145 × 235 mm; uterus coils situated in between anterior margin of ovary and posterior margin of ventral sucker, then passes dextrally along gargin of cirrus-sac to genital pore without coiling; eggs operculate, with with short, unipolar filament, 45-53 × 29-33 mm; vitelline follicles usually extending into the forebody. The new Helicometra species differ from other species in a combination of several morphometric and morphological characteristics: oesophagus short, distinct; genital pore antero-ventral to intestinal bifurcation and posterior margin of pharynx and eggs operculate, with short, unipolar filament. Opecoelus haduyngoi sp. n.: Body elongate-oval, 2,020-2,350 mm; maximum width in region of ventral sucker, 720-880 mm; width to length ratio 1:2.67-3.04; oral sucker 140-210 × 190-250 mm; ventral sucker 285-315 × 335-390 mm; forebody 630 mm (26.8-31.2% of body length); prepharynx short, 15-40 mm; pharynx large, 100-125 × 135-225 mm, well developed; pharynx to oral sucker width ratio 1:1.1-1.4; oesophgus distinct; testes 2, in middle third of body, contiguous, anterior 225-240 × 315-375 mm, posterior 260-300 × 350-400 mm; post-testicular area 340-560 mm, 16.8-23.8% of body length; cirrus-sac distinct, small, encloses anterior portion of male terminal genitalia, anterior to intestinal bifurcation, 300-315 × 50-80 mm; external seminal vesicle large, saccular, 200-210 × 100-125 mm; pars prostatica long; ejaculatory duct short; genital pore antero-sinistral to intestinal bifurcation, about half way between posterior margin of pharynx and posterior limit of oesophagus, 350-400 from anterior end mm; ovary pre-testicular, indented at posterior margin, contiguous with anterior testis, 105-150 × 225-275 mm; uterine coils in between anterior margin of ovary and posterior margin of seminal vesicle; eggs oval, large, 75-88 × 50-63 mm; vitelline follicles usually extending into the forebody, 510-580 mm from anterior extremity, 21.7-28.7% of body length.